Nutritional techniques for reducing the environmental impact of intensive non-ruminant animal production (Research, Society and Development, 2020)
The objective of this study was to report and discuss new strategies applied to animal nutrition that can contribute to sustainable production, minimizing the excretion of pollutants, without damage to the quality and maximum performance of animals. According to the sustainability-related animal nutrition studies analyzed, it is possible to reduce the impact of environmental pollution through various nutritional strategies in order to maximize nutrient retention efficiency and decrease nutrient excretion. The use of the ideal protein concept together with the use of industrial amino acids can be used as a way to reduce nitrogen excretion in several species without impairing performance. The use of organic minerals in non-ruminant animals, as well as phytase and enzymes, contribute to the increase of nutrient absorption and utilization, while the nutritional plans are of fundamental importance for the proper balance of nutrients and the requirements of each animal. Parallel to this, although still recent, nutrigenomics studies may contribute to the best adjustment of requirements, taking into account the genetic factor. On the other hand, the techniques employed to reduce the production and emission of poultry litter, when combined with nutritional strategies, can lead to a reduction in the emission of pollutant gases, and maximization of litter quality, contributing to animal welfare.